Lindung nilai (Hedging) perspektif Islam: Komparasi Indonesia dan Malaysia - Suryani Suryani; Muhammad Anwar Fathoni (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2017)
Islamic Hedging is one of the instruments in financial management that is used to reduce the risks associated with price and currency movements. But in a conventional perspective, hedging involves the use of controversial derivative instruments in Islamic view. The noble objective of this hedging has been misunderstood for profit only. Therefore, the concept of hedging needs further discussion because of various interpretations of the meaning of it. This study found that the concept of hedging according to Islam is different from the concept of conventional hedging. In addition, there are differences in the use of contracts in Islamic Hedging in Indonesia and Malaysia.